2015
DOI: 10.1002/poi3.110
|View full text |Cite
|
Sign up to set email alerts
|

The Unheavenly Chorus: Political Voices of Organized Interests on Social Media

Abstract: This study provides a descriptive look at the use of social media and the inequality of political voices in the context of political interest organizations. It seeks to answer the question of whether the Internet and social media allow those who were previously outside the power mainstream with respect to the broader democratic discourse to raise their voices and be heard. Overall, we find that social media does not diminish the concentration of political voices within the discourse. Rather, the evidence sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…An interesting observation is, however, that not all politicians may have perceived the benefits of this new media technology; some politicians actively engage in the adoption of online information technologies, while others lag far behind. In this study, we explore why we observe this variation in the ways politicians use social media-an Internet-based information technology often hailed as transformative on the level of previous innovations such as radio and television (Hong & Nadler, 2016). We thus examine U.S.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting observation is, however, that not all politicians may have perceived the benefits of this new media technology; some politicians actively engage in the adoption of online information technologies, while others lag far behind. In this study, we explore why we observe this variation in the ways politicians use social media-an Internet-based information technology often hailed as transformative on the level of previous innovations such as radio and television (Hong & Nadler, 2016). We thus examine U.S.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Another strand of recent studies has also explored who are more likely to adopt and use social media. Some scholars have proposed that politicians who lack name recognition and resources (Auter & Fine, 2018;Conway, Kenski, & Wang, 2013;Esteve Del Valle & Borge Bravo, 2018;Larsson & Kalsnes, 2014; but see Hong, 2013;Hong & Nadler, 2016;and Scherpereel, Wohlgemuth, & Lievens, 2018 for different perspectives) tend to use social media more intensively. On the other hand, other studies suggest the opposite, showing that incumbents and better-financed candidates are likely to use social media more often.…”
Section: Politics On Social Mediamentioning
confidence: 99%
“…Riezebos et al (2011) detected no impact of social media on voting behaviour, but changes in political party perception were present, according to their analysis of an online questionnaire during the Dutch national elections in 2010. Hong and Nadler (2015) support findings from Hindmann (2009) that the rate of political mobilisation is not increased through the use of the Internet, stating that online political voices are mostly made up of a small number of large organisations and networks (see also van der Graaf et al 2016). In the course of a literature review, Dini and Saebø (2016) make the observation that social media does not take the role of mobilising and creating participation if there is no active community already in place and that challenges such as exclusion, information misuse, deliberate misinformation, security threats, data leaks and privacy issues must be considered when social media is employed.…”
Section: Effects On Political Opinion and Behaviour: Inconclusive Resmentioning
confidence: 99%
“…Van der Graaf et al (2016) also find an evidence in favour of the resource-based hypothesis, suggesting that there is a positive correlation between staff size and social media use. Observing the political voice of interest groups in the United States of America, Hong and Nadler (2016) concluded that the bias observed in the offline lobbying world is no better in the online lobbying world. Chalmers and Shotton (2016) approach interest groups' social media use from a different angle.…”
Section: Literature Reviewmentioning
confidence: 99%